Zygomatic-orbital reconstruction in patient with Treacher Collins syndrome using bioceramic made of hydroxyapatite and β-tricalcium phosphate - Corrêa, A. P.S. [UNESP]; Shinohara, E. H. [UNESP]; Gavina, R. S.; Garcia-Júnior, I. R. [UNESP]; Timóteo, C. A. [UNESP] (Wiley, 2016)
Treacher Collins syndrome (TCS) is a rare, serious congenital malformation that mainly affects craniofacial structures, and the incidence of this syndrome is one in every 50 000 births. Craniofacial rehabilitation in patients with TCS generally includes zygomatic-orbital and maxillomandibular reconstruction. This article describes a case of TCS in which zygomatic-orbital reconstruction was performed with a third-generation, biphasic, micro-macro porous bioceramic composed of hydroxyapatite and beta-tricalcium phosphate. This method proved to be a viable alternative to autogenous grafts and led to a satisfactory aesthetic outcome.
Keywords: Bioceramic; Hydroxyapatite; Treacher Collins syndrome; β-tricalcium phosphate